2016
DOI: 10.2463/mrms.tn.2015-0081
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Intracranial Vasculatures in Healthy Subjects with Arterial-Spin-Labeling-Based 4D-MR Angiography at 3T

Abstract: Contrast inherent inflow-enhanced multi-phase angiography combining multiple-phase flow-alternating inversion-recovery (CINEMA-FAIR) is an arterial-spin-labeling-based four-dimensional magnetic resonance angiography (4D-MRA) technique. Two neuroradiologists independently evaluated the depiction of the intracranial vasculatures in healthy subjects with 3T 4D-MRA using CINEMA-FAIR. Our results indicated that this technique can provide good visualization of the cerebral arteries with a high spatial and temporal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…24 In 4D CTA, images are taken throughout the administration of a contrast bolus, whereas 4D MRA can be performed with or without contrast administration. 16,18,19,24,40,41 Although the initial experience with 4D MRA involved contrast administration, noncontrast-enhanced sequences such as 4D arterial spin-labeling MRA and 4D TOF have been developed, thus avoiding any potential complications from the use of contrast. 19,40,41 Multiple studies have shown that both contrast-enhanced and non-contrast-enhanced 4D MRA can quantify the degree of collateral circulation to an extent comparable with DSA, which is considered the gold standard.…”
Section: Four-dimensional Cta and Mramentioning
confidence: 99%
See 1 more Smart Citation
“…24 In 4D CTA, images are taken throughout the administration of a contrast bolus, whereas 4D MRA can be performed with or without contrast administration. 16,18,19,24,40,41 Although the initial experience with 4D MRA involved contrast administration, noncontrast-enhanced sequences such as 4D arterial spin-labeling MRA and 4D TOF have been developed, thus avoiding any potential complications from the use of contrast. 19,40,41 Multiple studies have shown that both contrast-enhanced and non-contrast-enhanced 4D MRA can quantify the degree of collateral circulation to an extent comparable with DSA, which is considered the gold standard.…”
Section: Four-dimensional Cta and Mramentioning
confidence: 99%
“…16,18,19,24,40,41 Although the initial experience with 4D MRA involved contrast administration, noncontrast-enhanced sequences such as 4D arterial spin-labeling MRA and 4D TOF have been developed, thus avoiding any potential complications from the use of contrast. 19,40,41 Multiple studies have shown that both contrast-enhanced and non-contrast-enhanced 4D MRA can quantify the degree of collateral circulation to an extent comparable with DSA, which is considered the gold standard. 16,18 Improved collateral flow surrounding an area of ischemia has been associated with better rates of recanalization, a lower incidence of hemorrhagic transformation, and improved clinical outcome after both thrombectomy and thrombolytic administration.…”
Section: Four-dimensional Cta and Mramentioning
confidence: 99%
“…Furthermore, ASL-MRA allows dynamic signal collection with appropriate timing delays after labeling to achieve 4D MRA with temporal information, which is not possible with TOF and was previously only possible with conventional angiography [14,[19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%